Killing, karma and caring: euthanasia in Buddhism and Christianity. - Keown, D (1995)
In 1993 The Parliament of the World's Religions produced a declaration known as A Global Ethic which set out fundamental points of agreement on moral tissues between the religions of the world. However, the declaration did not deal explicitly with medical ethics. This article examines Buddhist and Christian perspectives on euthanasia and finds that in spite of their cultural and theological differences both oppose it for broadly similar reasons. Both traditions reject consequentialist patterns of justification and espouse a 'sanctity of life' position which precludes the intentional destruction of human life by act or omission.